The Impact of Community-Driven Educational Policies on Achieving Equity for Marginalized Students - Lila Nasruden; Neil Rey (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study explores the impact of community-driven educational policies on achieving equity for marginalized students. By examining several case studies across diverse educational environments, the research highlights how community involvement in decision-making, culturally relevant curriculum design, and the removal of structural barriers contribute to improved academic performance and social outcomes. Findings indicate that community engagement enhances student participation, academic achievement, and behavior, leading to decreased dropout rates and a positive school climate. Furthermore, the study emphasizes the role of culturally responsive pedagogy in fostering a sense of belonging among marginalized students, thus strengthening the connection between schools and local communities. The results suggest that community-driven policies are a powerful tool for reducing educational disparities and promoting a more inclusive and equitable educational experience for all students. Future research should investigate the long-term sustainability of these practices and their broader implications for global education systems.